Multiphase characterization of wild Vigna associated root nodule bacteria from Japanese subtropical islands unveiled novel high temperature resistant Bradyrhizobium strains having high symbiotic compatibility with soybean and mungbean. Issue 2 (3rd March 2020) - Mortuza, Md Firoz; Tomooka, Norihiko; Habibi, Safiullah; Akatsu, Tetsuya; Djedidi, Salem; Naito, Ken; Sekimoto, Hitoshi; Okazaki, Shin; Ohkama-Ohtsu, Naoko; Yokoyama, Tadashi
ABSTRACT: Vigna riukiuensis plant – a rare type of vigna, found only in Taiwan and the islands of Okinawa prefecture, Japan – possesses intrinsic property of high level of salt and heat tolerance. To understand the diversity and identify suitable rhizobia, multiphase characterization of root nodule bacteria associated with V. riukiuensis grown in Ishigaki and Iriomote Islands of Okinawa prefecture was performed. Multigene phylogenetic analysis of housekeeping genes based on 16S rRNA gene sequences, 16S-23S rRNA gene internal transcribed spacer (ITS) and 23S rRNA gene sequences identified three main groups closely similar to Bradyrhizobium japonicum, B. elkanii and B . jicamae family. However, analysis of symbiotic nifH and nodD1 genes and their phylogenetic trees showed similar topology, having only few discrepancies in comparison to the housekeeping gene phylogeny. Interestingly, for some of the isolates having similarity with B. elkanii, growth was observed at 40°C, which exceed the highest record for B. elkanii to the best of our knowledge. All the isolates were observed to have the capability of forming root nodules and fix nitrogen in their original host plant V. riukiuensis and two other crops: soybean and mungbean. Most of the isolates showed similar or higher nitrogen-fixing capability in comparison with B . diazoefficiens USDA110 in V. riukiuensis and V. radiata (mungbean), and Iri 5/6 in V. riukiuensis, Iri 5/12 in soybean and Ishi 7/2 in mungbean showed highest acetylene reduction assay (in µmol/h/gm nodule dry weight) activity, which was significantly higher than B. diazoefficiens USDA110. In addition, six isolates attained higher soybean biomass production compared with B. diazoefficiens USDA110, suggesting high symbiotic compatibility with soybean. Among them, Iri 5/7 of B. elkanii group contributed 29% higher soybean biomass production than B. diazoefficiens USDA110 and could grow at 40°C, hence it could be a promising soybean inoculant in the tropics. Abbreviations: ARA: acetylene reduction assay, ISR: intergenic spacer regions, ITS: internal transcribed spacer